MODEL VALUE CLARIVICATION TECHNIQUE GAMES PADA PEMBELAJARAN PKN - Asis Saefudin; Siti Aminah Sya’baniyah (Al-Aulad: Journal of Islamic Primary Education, 2018)
The purpose of this study is to determine the use of value model clarification technique games on learning civics and knowing student learning outcomes. The method used in this research is correlation method. The collect data by observation, questionnaire, and test. Respondents in this study as many as 22 students of grad three Islamic primary school Darul Hufadz Sumedang District West Java Indonesia. To analyze the data used two approaches namely partial analysis and correlational analysis. The result of the analysis shows that value clarification technique games model in civics learning is included in the high category with the average value 3,76. The student learning outcomes subject matter of the importance of self-esteem included in both categories with an average value of 70.90. The relationship between the two is shown by the correlation coefficient of 0.66, which is included in the category enough. The result of t-test at 5% significance level shows the price of t arithmetic (3.933)> t table (1.725). It means Ha accepted that there is a significant positive relationship between value clarification technique games model on learning civics with a student learning outcomes subject matter of the importance of self-esteem. The level of influence of variable X to variable Y by 25%. Thus, apart from the value factor model Clarification Technique Games on learning Civics, it is still there are 75% other factors that affect student learning outcomes.